Relation Between Soft Drink Consumption And Obesity In Adolescents - Halim, Yeni; Sembiring, Tiangsa; Sianturi, Pertin; Faranita, Tri; Pratita, Winra (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study examines the relationship between soft drink consumption and obesity among adolescents. Obesity, a critical public health issue, has shown a rising prevalence globally, including in Indonesia, due to changes in dietary patterns and lifestyle. The research adopts a cross-sectional design conducted at Santo Thomas 1 Private High School in Medan, involving 198 students categorized into obese and non-obese groups based on Body Mass Index (BMI). The findings reveal that frequent soft drink consumption (more than three times a week) significantly increases the risk of obesity (p = 0.0001). Additionally, low physical activity and excessive caloric intake were identified as major contributing factors. Multivariate analysis highlighted low physical activity as the dominant risk factor for obesity, with an odds ratio of 36.351. The study underscores the need for targeted interventions to reduce soft drink consumption and promote healthier lifestyle choices among adolescents to mitigate the adverse effects of obesity on health outcomes.